Description of Cribronema sturhani sp. n. (Nematoda, Rhabditida, Cephalobidae), a second species of a rare genus from Cameroon - Boström, Sven; Holovachov, Oleksandr (Zootaxa, 2019)
Specimens of a population of Cribronema collected in Cameroon are described as Cribronema sturhani sp. n. The new species resembles C. cribrum, which is the only species described in the genus, but it differs from it by the following features: a somewhat shorter tail in the females, longer spermatheca and postuterine vulval sac, tail terminus in females pointed vs. harpoon-shaped, and presence vs. absence of males.